The biosynthesis and regulation of isoprenoids - HAO Hong-lei; ZHU Xu-fen; ZENG Yun-zhong (浙江大学学报. 农业与生命科学版, 2002)
Isoprenoids constitute a chemically diverse family of naturally occurring compounds with a common structural five-carbon unit, the isoprene. This review presents the biosynthetic pathway of isoprenoids and the primary enzymes incolued. The current researches on nelevant genes and regulation of their actions are also conversed.